Feasibility and efficacy of a multicomponent exercise medicine programme in patients with pancreatic cancer undergoing neoadjuvant therapy (the EXPAN trial): study protocol of a dual-centre, two-armed phase I randomised controlled trial - Hao Luo; Robert U Newton; Daniel A Galvão; Dennis R Taaffe; Andrew Dean; Nigel Spry; Colin Tang; Kevin Jasas; Mikael Johansson; Ian Yusoff (BMJ Open Gastroenterology)
Introduction Exercise is emerging as a therapy in oncology for its physical and psychosocial benefits and potential effects on chemotherapy tolerability and efficacy. However, evidence from randomised controlled trials (RCTs) supporting exercise in patients with borderline resectable or locally advanced pancreatic cancer (PanCa) undergoing neoadjuvant therapy (NAT) are lacking.Methods and analysis The EXPAN trial is a dual-centre, two-armed, phase I RCT. Forty patients with borderline resectable or locally advanced PanCa undergoing NAT will be randomised equally to an exercise intervention group (individualised exercise+standard NAT) or a usual care control group (standard NAT). The exercise intervention will be supervised and consist of moderate to vigorous intensity resistance and aerobic-based training undertaken two times a week for 45–60 min per session for a maximum period of 6 months. The primary outcome is feasibility. Secondary outcomes are patient-related and treatment-related endpoints, objectively measured physical function, body composition, psychological health and quality of life. Assessments will be conducted at baseline, prior to potential alteration of treatment (~4 months postbaseline), at completion of the intervention (maximum 6 months postbaseline) and 3-month and 6-month postintervention (maximum 9 and 12 months postbaseline).Ethics and dissemination The EXPAN trial has been approved by Edith Cowan University (reference no.: 2020-02011-LUO), Sir Charles Gairdner Hospital (reference no.: RGS 03956) and St John of God Subiaco Hospital (reference no.: 1726). The study results will be presented at national/international conferences and submitted for publications in peer-reviewed journals.Trial registration number ACTRN12620001081909.